2005
DOI: 10.1007/s00441-005-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

The complexus adhaerens of mammalian lymphatic endothelia revisited: a junction even more complex than hitherto thought

Abstract: The significance of a special kind of VE-cadherin-based, desmoplakin- and plakoglobin-containing adhering junction, originally identified in certain endothelial cells of the mammalian lymphatic system (notably the retothelial cells of the lymph node sinus and a subtype of lining endothelial cells of peripheral lymphatic vessels), has been widely confirmed and its importance in the formation of blood and lymph vessels has been demonstrated in vivo and in vitro. We have recently extended the molecular and struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 94 publications
1
52
0
Order By: Relevance
“…Localization of claudin-5, JAM-A, JAM-C, ESAM-1 and ZO-1 characterizes the molecular composition of tight junctions between the sinus-lining endothelial cells of the subcapsular and medullary sinuses and provides the molecular basis for the diffusion barrier established at this level. Our findings are in agreement with a previous study, which reported the presence of unique cell contacts between sinus-lining endothelium, designated complexus adhaerens in human lymph nodes [30]. The name complexus adhaerens was coined to describe this specific cell-tocell-contact, combining molecular elements from adherens junctions such as VE-cadherin, a-and b-catenin, with prominent desmosomal plaque proteins such a desmoplakin and plakoglobin and several tight junction proteins such as claudin-5, JAM-A and ZO-1.…”
Section: Discussionsupporting
confidence: 94%
“…Localization of claudin-5, JAM-A, JAM-C, ESAM-1 and ZO-1 characterizes the molecular composition of tight junctions between the sinus-lining endothelial cells of the subcapsular and medullary sinuses and provides the molecular basis for the diffusion barrier established at this level. Our findings are in agreement with a previous study, which reported the presence of unique cell contacts between sinus-lining endothelium, designated complexus adhaerens in human lymph nodes [30]. The name complexus adhaerens was coined to describe this specific cell-tocell-contact, combining molecular elements from adherens junctions such as VE-cadherin, a-and b-catenin, with prominent desmosomal plaque proteins such a desmoplakin and plakoglobin and several tight junction proteins such as claudin-5, JAM-A and ZO-1.…”
Section: Discussionsupporting
confidence: 94%
“…Clearly, our finding of ezrin as a major cytoskeletal component in MSC processes should now lead to investigations regarding its presence and fuction in the formation of processes of mesenchymal cells during early embryogenesis or in adhering junction-stabilized cytoplasmic projections of retothelial cells of the sinus of lymph nodes (cf. Hämmerling et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The sinus lining cells are linked by junctions termed "complexus adhaerentes" (Schmelz et al, 1994). Recently, Hämmerling et al (2006) showed that the complexus adhaerentes of mammalian lymphatic endothelia comprises zonula adherens proteins (VEcadherin, -and -catenin, protein p120 ctn , and afadin), desmosomal plaque components (desmoplakin and plakoglobin) and tight-junction proteins (claudin-5 and ZO-1).…”
Section: Lymph Node Structure and Functionmentioning
confidence: 99%